2017
DOI: 10.1111/obes.12161
|View full text |Cite
|
Sign up to set email alerts
|

Do Smaller Classes Always Improve Students’ Long‐run Outcomes?

Abstract: We exploit the strict class size rule in Norway and matched individual and school register information for 1982-2011 to estimate long-run causal effects on income and educational attainment. Contrary to recent evidence from the US and Sweden, we do not find any significant average effect on long-run outcomes of reduced class size. We further use the large register data set and quasi-experimental strategy to estimate whether the class size effect depends on external conditions facing students and schools, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 84 publications
(116 reference statements)
3
20
0
1
Order By: Relevance
“…Recently Fredriksson et al (2013Fredriksson et al ( , 2014, using Swedish data, were the first to report statistically significant effects on earnings and find that a 1 pupil decrease leads to 1.5 percentage point increase in earnings. A recent study using Norwegian data by Falch et al (2017) do not find any significant beneficial long-term effects from a middle school class size reduction, consistent with the absence of effects in Leuven et al (2008).…”
Section: Introductionmentioning
confidence: 61%
“…Recently Fredriksson et al (2013Fredriksson et al ( , 2014, using Swedish data, were the first to report statistically significant effects on earnings and find that a 1 pupil decrease leads to 1.5 percentage point increase in earnings. A recent study using Norwegian data by Falch et al (2017) do not find any significant beneficial long-term effects from a middle school class size reduction, consistent with the absence of effects in Leuven et al (2008).…”
Section: Introductionmentioning
confidence: 61%
“…This allows the teachers to pay more attention to each child and gives a greater opportunity for the student to be active. Comprehensive research has true enough not been able to find unequivocal links between class size and student achievement (Falch, Sandsør & Strøm, 2017). At the same time, studies have shown increased learning outcomes from teaching in small student groups (Elbaum, Vaughn, Hughes & Moody, 1999;Vaughn et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings can be compared with evidence in Leuven, Oosterbeek and R⊘nning () and Falch et al . () indicating that supply‐side policies such as class size reductions have negligible effects on short‐term outcomes (test scores) and long‐term outcomes (educational attainment) in Norway. Taken literally, this finding suggests that education policy discussions should be relatively more concentrated on possible demand‐side problems and student incentives than on traditional supply‐side policies.…”
Section: Discussionmentioning
confidence: 99%